Real time STM observation of Au-assisted decomposition of SiO2 films on Si(111) at elevated temperatures - Jun, W; Mitchell, C; Egdell, R; Foord, J (2002)
The decomposition of ultrathin layers of SiO2 on Si(1 1 1) has been studied in real time in a high temperature scanning tunnelling microscope. Deposition of Au onto the SiO2 surface lowers the temperature of decomposition from 1000 to 940 K. Film decomposition takes place initially at step edges. The mechanism is shown to involve nucleation of Au nanoparticles at step edges, "sinking" of the Au particles to the buried SiO2/Si interface and accelerated reaction of substrate Si with SiO2 around Au nuclei. The Au/Si surface left after film decomposition supports a row-like reconstruction with a periodicity six times that of Si(1 1 1). © 2002 Published by Elsevier Science B.V.